2011
DOI: 10.1136/jcp.2010.080820
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in obtaining and interpreting bone marrow aspirates: to err is human

Abstract: Pitfalls relating to bone marrow aspirates and their interpretation start even before the aspirate is obtained. There can be failure to perform an aspiration that is clinically indicated or, conversely, an aspiration may be done that is not actually necessary. Once an aspirate is obtained it may be unhelpful because it is a blood tap or very dilute, or because of the sampling error that is intrinsic to the procedure. Even if an adequate aspirate is obtained, it may be misinterpreted. Megaloblastic marrows and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Accordingly, there may also be treatment-induced changes in MRD marker profile or undetected subclones at diagnosis and thus failure to detect or underestimation of residual disease. Furthermore, contribution of bone microenvironment, cell adhesion and cell stroma interactions may also influence sample quality (17)(18)(19). To a certain extent, this may be overcome by always combining aspiration with trephine biopsy and touch imprint preparations (17,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, there may also be treatment-induced changes in MRD marker profile or undetected subclones at diagnosis and thus failure to detect or underestimation of residual disease. Furthermore, contribution of bone microenvironment, cell adhesion and cell stroma interactions may also influence sample quality (17)(18)(19). To a certain extent, this may be overcome by always combining aspiration with trephine biopsy and touch imprint preparations (17,20).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, contribution of bone microenvironment, cell adhesion and cell stroma interactions may also influence sample quality (17)(18)(19). To a certain extent, this may be overcome by always combining aspiration with trephine biopsy and touch imprint preparations (17,20). BM touch imprints and trephine biopsies play a crucial role in the diagnostic workup of acute leukemia, particularly when there are severe pancytopenia and a dry tap or a bloody tap on BM aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…While it is problematic that 38.7% of published RCTs that receive detailed review are found to have methodological issues (Table 4), this finding must be kept in context. Research proceeds by trial and error (6), so to err in clinical medicine is human (35). However, as medical decision making profoundly affects patients, clinicians cannot be complacent about the validity of RCTs for guiding clinical decision making (36).…”
Section: Discussionmentioning
confidence: 99%
“…If the BM sample does not contain the lesion, no special studies could compensate for the deficiency of proper sampling . Therefore, general guidelines for BM biopsy should be followed in the first place . Recommendation 3 . It is recommended that the interpretation starts with the evaluation of the external control(s), by which it is determined that the proper antibody was applied and the test is properly calibrated. Recommendation 4 .…”
Section: Recommendationsmentioning
confidence: 99%